Low‐grade tumour over the left temporal neocortex and ictal asystole: network and surgical implications. Issue 5 (16th November 2021) - Russo, Angelo; Francione, Stefano; Martinoni, Matteo; Zucchelli, Mino; Guerra, Angelo; Terrone, Gaetano; Del Giudice, Ennio; Gobbi, Giuseppe
Abstract: We describe a patient with focal epilepsy characterized by ictal asystole episodes and low‐grade tumour over the left temporal neocortex. Non‐invasive pre‐surgical evaluation showed an epileptogenic zone extended beyond the low‐grade tumour. This extension was confirmed by intraoperative electrocorticography. One‐stage surgery with anterior temporal lobe resection was performed. The patient was seizure‐free after one year of follow‐up. Detailed electroclinical and therapeutic reasoning with hypotheses defining epileptogenic and symptomatogenic networks are discussed.